Od metropolii podzielonej do metropolii zjednoczonej – kształtowanie się tożsamości instytucji metropolitalnego zarządzania w kontekście relacji miast górnośląskiego obszaru metropolitalnego - Neuve-Église, Zuzanna (Człowiek i Społeczeństwo, 2023)
The Upper Silesian conurbation is a unique area in Poland due to its polycentric nature, expressed in the interaction of a group of cities. The paper describes the transformation of the image of the “metropolis” in the Silesian Voivodeship, addressing the issues of complex relations between the cities of the Upper Silesian Metropolitan Area. The results of the qualitative content analysis of strategic programs of the municipalities participating in the metropolitan union since 2017 highlighted two main categories of the concept of “metropolis” – a chance and a threat. Then, the selected aspects shaping the identity of the institution of metropolitan management were demonstrated based on the regional press discourse analysis. Thus, this paper explores a path of metropolitan integration of the municipalities in the face of the emergence of a new metropolitan institution – from rivalry tendencies based on the historical and cultural divisions of the region and the revival of local identities to conciliatory attitudes.